2011
DOI: 10.1111/j.1475-6765.2010.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravitation or discrimination? Determinants of litigation in the World Trade Organisation

Abstract: The strong presence of large countries in World Trade Organisation (WTO) dispute settlement and the absence of very poor ones have raised concerns that increasing legalisation in the global trading system has not diminished discrimination against less powerful countries as much as expected. This article examines dispute initiations in all WTO member state dyads in 1995–2003 to shed more light on this issue. The analysis suggests that the main driver of dispute initiation is a gravitational one: larger economie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…A first control variable is for regime type, since studies have found that democratic states are more likely to embrace legal dispute settlement to settle disputes (e.g., Allee and Huth 2006;Gomez-Mera and Molinari 2014;Sattler and Bernauer 2011). By extension, one would expect that democratic states will be more receptive to the inclusion of strong, legal dispute settlement language in their agreements.…”
Section: Conceptualization and Measurement Of Independent Variablesmentioning
confidence: 99%
“…A first control variable is for regime type, since studies have found that democratic states are more likely to embrace legal dispute settlement to settle disputes (e.g., Allee and Huth 2006;Gomez-Mera and Molinari 2014;Sattler and Bernauer 2011). By extension, one would expect that democratic states will be more receptive to the inclusion of strong, legal dispute settlement language in their agreements.…”
Section: Conceptualization and Measurement Of Independent Variablesmentioning
confidence: 99%
“…Sattler and Bernauer 2011. See Allee 2005Allee , 2010aAllee , and 2010bBown 2005a;Busch, Reinhardt, and Shaffer 2009;Davis and Bermeo 2009;Kim 2008;and Sattler and Bernauer 2011. smaller states resemble relatively easy targets for retaliatory measures when litigating against a large trading partner because they depend more strongly on exports to rich and large markets. This adds to existing concerns about the effectiveness of the WTO dispute settlement procedure in that it may fail to enable disadvantaged countries to effectively proceed against a discriminating trading partner and achieve the removal of illegal trade barriers.…”
Section: Dispute Settlement In the International Trade Systemmentioning
confidence: 99%
“…Algunas de ellas, como poder económico (Sattler & Bernauer, 2011), capacidad legal (Busch, Reinhardt & Shaffer, 2008;Conti, 2010), diversidad y valor de las exportaciones (Horn, Mavroidis & Wijkström, 1999;Holmes, Rollo & Young, 2003) y disponibilidad de recursos financieros, humanos e institucionales (Bohl, 2009;Guzmán & Simmons, 2005), sugieren una relación entre el nivel de desarrollo del país y la frecuencia con que este recurre al OSD. De hecho, Leitner & Leister (2013) después de analizar las principales tendencias en el total de disputas ante la OMC entre 1995 y 2012 que Estados Unidos y la Unión Europea serían por lejos los miembros con mayor participación como reclamantes, así como demandados, ante el OSD.…”
Section: C) Diferenciasunclassified